2014
DOI: 10.1149/05845.0021ecst
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Gas Composition Just before Fuel Pulses on Power Generation Characteristics at Different Fuel Supply Frequency in Pulse Jet-Rechargeable Direct Carbon Fuel Cells

Abstract: Pulse Jet - Rechargeable Direct Carbon Fuel Cells (PJ-RDCFCs), in which small amounts of liquid hydrocarbon are supplied by pulse jet, were found to show different power generation characteristics depending on the time interval between fuel pulses (T int). For the T int range studied here (1 to 210 sec), both the maximum terminal voltage during a single cycle and the increase rate just after a fuel pulse can be controlled by T int, and this T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Previously, we estimated the relationship between U fuel and the reactions in each cycle from electrochemical measurements in the PJ-SOFCs. 40,41 When U fuel is set at a sufficiently small value, PJ-SOFC power generation involves the thermal decomposition of both isooctane and hydrocarbon (Eqs. 3 and 4), which have high partial pressures, and the direct electrochemical reaction of hydrocarbon fuel (Eq.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, we estimated the relationship between U fuel and the reactions in each cycle from electrochemical measurements in the PJ-SOFCs. 40,41 When U fuel is set at a sufficiently small value, PJ-SOFC power generation involves the thermal decomposition of both isooctane and hydrocarbon (Eqs. 3 and 4), which have high partial pressures, and the direct electrochemical reaction of hydrocarbon fuel (Eq.…”
Section: Resultsmentioning
confidence: 99%
“…The relationship between U fuel and the reactions in the PJ-SOFC are described above. 40,41 In the present study, U fuel,end was fixed at 60%. Therefore, Eqs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Isooctane was used as the fuel in this study because power generation characteristics have been reported for PJ-RDCFCs using isooctane as the gasoline model as fuel (15,16).…”
Section: Fabrication Of Fuel Cellsmentioning
confidence: 99%
“…Gas composition in the anode changes because thermochemical reactions and electrochemical reactions occur between pulses, and thus the chemical species that contribute significantly to the electrochemical reactions in PJ-RDCFCs react selectively. Consequently, the type of chemical species that react can be selected by controlling the fuel supply frequency (16). Though the amount of deposited carbon on the anode increases due to sulfur, there is a possibility that carbon deposition can be controlled by adjusting the operating conditions in which carbon is more contributive to the electrochemical reactions.…”
Section: Introductionmentioning
confidence: 99%